Police brutality in Greece: the rotten tree - Tsukala, Anastasia (Explosive politics, 2025)
"The book addresses police brutality from an angle still unexplored in academia. In opting for an interactionist approach, it focuses on a multi-actor field, the police-government-justice nexus, to show how its dynamics impact on police brutality, deactivate its control and create political and legal disorder. Crosschecking police officers' motivational patterns with public discourses, the rationale of internal and criminal investigations, Court's rulings and rank-and-file accountability-avoiding practices shows how their interaction ensures quasi-impunity that allows excessive force to become perennial. Analysis of the manifestation and handling of police brutality in 136 cases is grounded, inter alia, on 128 interviews conducted with victims of excessive force - lawmakers, presspersons, attorneys, protesters, ordinary civilians, members of socially vulnerable groups - or their attorneys and eyewitnesses"-- Provided by publisher